PEMBERDAYAAN MASYARAKAT DESA LARANGAN DALAM PRODUKSI SABUN PEMBERSIH MENGGUNAKAN ECO ENZYM - Nestri Widyastuti; Wasilatur Rahmah; Puspito Wulandari PPM; Darsih; Venny Dwi Yulianti; Ifadhotur Rohmah,; Siti Asma’ul Khusnah; Okty Parisa; Asmaryanti; Suparti; Milawati; Pismia Sylvi; Tiara Sevi Nurmanita; Muhammad Yusron Maulana El-Yunusi (AlMurtado Journal of Social Innovation and Community Service, 2025)
Organic waste is one type of garbage that often arises from daily human activities, and currently, households are one of the largest contributors of waste in Indonesia. Therefore, without proper management, it can become an environmental issue. In this community service activity, as a form of environmental concern, a community empowerment program was created for processing Eco Enzyme into derivative products for the PKK group of RT 45, Larangan Village, Sidoarjo, in the form of cleaning soap. The community service activity is carried out by implementing the ABCD (Asset Based Community Development) model, which focuses on Discovery (Potential), Dream (Dreams), Design (Strategies implemented), Define (Short-term activity focus), Do (Work program implementation plan). This approach involves a participatory process where community members actively play a role in identifying resources, skills, and potentials they possess. This activity process involves several stages, including socialization, demonstration, and practice. The outcome of community empowerment is expected to provide positive impacts for the residents of RT 45, where by producing Eco Enzyme derivative products into cleaning soap, family shopping budgets can be saved.